Election Night for Chris Petersen and Les Kimber - Watkins, Howard::::::::: (1983)
Seated: ?, Chris Petersen; Standing: Dirk Van Gelder, Laurie ?, Bill Riddlesprigger, Bob Lincon, Bob Lung, ?, Valerie Lung, ??, Rod Haron, Betty Haron, Clyde Jones, ????